Stochastic processes on non-Archimedean Banach spaces - S. V. Ludkovsky (International Journal of Mathematics and Mathematical Sciences)
Non-Archimedean analogs of Markov quasimeasures and stochastic processes are investigated. They are used for the development of stochastic antiderivations. The non-Archimedean analog of the Itô formula is proved.